Caution When Assessing Immunity to Varicella Through Antibody Testing in Patients with Inflammatory Bowel Disease. Issue 10 (October 2017) - Caldera, Freddy; Wasan, Sharmeel K.; Farraye, Francis A.; Hayney, Mary S.
Abstract : Article first published online 5 september 2017.